Analysis of community-acquired COVID-19 cases in Taiwan. Issue 12 (12th August 2020) - Liu, Jui-Yao; Chen, Tzeng-Ji; Hwang, Shinn-Jang
Abstract : Background: The demographic characteristics and transmission dynamics of the community-acquired coronavirus disease 2019 (COVID-19) cases in Taiwan were analyzed for more effective control and prevention of the community transmission of this novel disease. Methods: Open-access data and press releases on COVID-19 in Taiwan were collected on the website of the Taiwan Centers for Disease Control. All 55 community-acquired cases of COVID-19 confirmed from January 28 to April 12, 2020, in Taiwan were included. Basic demographic characteristics, symptom presentation, infection source, route of identification, and transmission dynamics were analyzed. Results: Of the 55 cases, 52.7% were female and 74.5% were between 20–59 years of age. One-sixth (16.4%) of community-acquired cases were asymptomatic. More than half (58.2%) of the cases were identified via contact tracing. The median incubation period was 6 days (range 1-13 d) and the median serial interval was 4 days (range −3-24 d). Twenty-six cases (47.3%) were transmitted from presymptomatic cases, 11 cases (20%) from symptomatic cases, and 2 cases (3.6%) from an asymptomatic case. The contagious period of symptomatic cases was from 7 days before to 15 days after the onset of symptoms. Conclusion: The high proportion of asymptomatic cases and the transmissibility in the presymptomatic and asymptomatic periods make control of COVID-19 challenging. Protective measures such as social distancing, wearing face masks, and hand washing are mandatory to prevent community transmission.